One Lung Ventilation (OLV) on Needle Evacuation Thoracotomy in Pediatric Patient - Hariyanto, Achmad; Hadi Pratama, Muhamad Rizal; Alami, Eqiel Navadz Akhtar (Faculty of Medicine, Brawijaya University, 2023)
Background: One lung ventilation (OLV) is a ventilation method that functions to facilitate surgery on one side of the lung to protect one of the lungs from exposure to fluids such as blood, secretions, or foreign bodies. Therefore, it is necessary to place the endrotracheal tube correctly so that complications do not occur. This case report aims to determine the success in surgery using OLV method with blind insertion in pediatric patient.Case: A 10 years old male patient came to the hospital with complaints of sore throat. Thorax X-Ray photo examination showed that there was a needle-shaped corpus alienum density in the right bronchus branch of the orificium of the right lung. The patient was planned for a needle evacuation thoracotomy using a Double lumen endotracheal-tube (DLT) size 26. The patient was induced using the total intravenous anaesthesia (TIVA) method, ventilation using OLV. The operation was carried out with an incision at the 8th posterolateral intercostal space (ICS) of the dextra deepened layer by layer, the pleura was bluntly penetrated. This surgery went success to extract needle and the patient's condition was stable (HR=104x/min, SpO2=95%). On a third day after surgery, the patient was stable and discharged.Conclusion: The OLV method using DLT in pediatric patient with blind insertion during thoracotomy showed good results with early mobilization on day 1 after surgery, 3 days of hospital stays, and did not show any serious complication after surgery. Â